Perbandingan Faktor-Faktor Yang Menentukan Motivasi Kerja Pada Generasi X Dan Y - Afiga Putra Bhakti; Alexander Putra Kevin; Andrew Santos Alisuci; Beryl Putra Pratama (Universitas Prasetiya Mulya, 2019)
The present work environment is dominated by generation x and generation y that have different characteristics, therefore the factors that determine work motivation need to be investigated to find out the differences between generation x and generation y. This research is a quantitative research that begins with qualitative research to look for additional factors outside the theory, then the distribution of questionnaires is conducted to 100 respondents generation x and 100 respondents generation y, who are still working in a company and who had ever worked in a company. The results shown that there is no significant difference between the factors that determine the work motivation on generation x and generation y, except on the salary factor. In addition, there is interesting finding where the top factor in generation x and generation y are the hygiene factors. The study is time limited, therefore, there is a need for further research to explore regarding the finding of this study. This study is expected to be useful for employees of generation x and generation y, as well as for human resources departments in companies.